Effect of inter‐twin delivery interval on umbilical artery pH and Apgar score in the second twin. Issue 1 (2nd November 2017) - Tal, Alon; Peretz, Hadar; Garmi, Gali; Zafran, Noah; Romano, Shabtai; Salim, Raed
Abstract: Background: To examine the effect of inter‐twin delivery interval on umbilical artery pH and Apgar score of the second twin after vaginal delivery of the first twin. Methods: Retrospective study conducted at a single teaching hospital. All pregnant women with twin gestation who delivered the first twin vaginally at more than 24 weeks between 1995 and 2015 were included. Major malformations and intrauterine deaths of one or both twins were excluded. Women were divided into those who had an inter‐twin delivery interval of less than 30 minutes (group 1) or 30 minutes or more (group 2). Primary outcome was umbilical artery pH less than 7.1 and/or Apgar score less than 7 at 5 minutes of the second twin. Generalized linear regression with log was performed to evaluate the association with delivery interval. Results: Of 88 145 deliveries during this period, 1955 (2.2%) were twins. Overall, 713 twin pregnancies, 596 (83.6%) in group 1 and 117 (16.4%) in group 2, were eligible and included. Mean inter‐delivery interval was 11.0 ± 6.5 and 52.5 ± 31.5 minutes in groups 1 and 2, respectively. After adjusting for variables found significantly different between the groups in univariate analysis, inter‐delivery interval of less than 30 minutes or 30 minutes or more was not a significant risk factor for pH less than 7.1 and/or Apgar less than 7 ( P = .91). The cesarean rate for delivery of the second twin after vaginal delivery of the first twin was 4.3% overall, with a higher rate among group 2 compared with group 1 (18.2% and 3.2%, respectively; P = .001). Conclusions: The second twin's Apgar score and cord artery pH are probably not affected when the inter‐twin delivery interval exceeds 30 minutes.